An Investigation On The Properties Of Ferrocement Containing Different Layers Of Wire Mesh - Chan, Fun Sin (Universiti Sains Malaysia, 2006)
Ferrocement, a thin wall cement mortar reinforced with wire mesh and now considered to be a very innovative construction material, was known to be used over hundred years ago. Ferrocement is the most effective route to impart outstanding crack control to the concrete matrix and through this crack control, develop excellent mechanical properties, energy absorption characteristics, toughness and impact resistance. The principle of ferrocement is to understand it mechanism whereby the reinforcement and matrix interact to distribute strains, improve first crack strength and control the size and spacing of cracks. Numerous theoretical and experimental studies have been undertaken all over the world in recent years to investigate the properties of ferrocement and explore its potential field of applications. It is obviously unrealistic to talk about ferrocement replacing reinforced concrete for all the purposes, but it is undeniable that there are many situations where the use of the ferrocement concept can be more cost effective in terms of construction costs and its service life span. It is now clear that ferrocement, a versatile construction material, has a bright prospect and will definitely find better utilization in the future.